Evidence of methylation of B77 avian sarcoma virus genome RNA subunits. - Stoltzfus, C M (1976)
B77 avian sarcoma virus RNA was labeled with (methyl-3H) methionine under conditions that prevent non-methyl incorporation of 3H radioactivity into purine rings. From the determined values for the extent of methylation of 4S RNA isolated from infected chicken embryo cells, it was estimated that 30 to 40S RNA subunits that results from heat denaturation of the 60 to 70S RNA contain approximately 21 methyl groups, of which 14 to 16 are present at internal positions as N6 -methyladenosine residues. In addition, each of the virion RNA subunits appears to contain about two methyl groups in the "capped" 5' -terminal structure m7G(5')ppp(5') gm. These properties are consistent with the hypothesis that the 30 to 40S genome RNA os oncornaviruses also serves an mRNA function in infected cells.